Diffusion tensor imaging reveals adolescent binge ethanol‐induced brain structural integrity alterations in adult rats that correlate with behavioral dysfunction. (11th February 2015) - Vetreno, Ryan P.; Yaxley, Richard; Paniagua, Beatriz; Crews, Fulton T.
Abstract: Adolescence is characterized by considerable brain maturation that coincides with the development of adult behavior. Binge drinking is common during adolescence and can have deleterious effects on brain maturation because of the heightened neuroplasticity of the adolescent brain. Using an animal model of adolescent intermittent ethanol [AIE; 5.0 g/kg, intragastric, 20 percent EtOH w/v; 2 days on/2 days off from postnatal day (P)25 to P55], we assessed the adult brain structural volumes and integrity on P80 and P220 using diffusion tensor imaging (DTI). While we did not observe a long‐term effect of AIE on structural volumes, AIE did reduce axial diffusivity (AD) in the cerebellum, hippocampus and neocortex. Radial diffusivity (RD) was reduced in the hippocampus and neocortex of AIE‐treated animals. Prior AIE treatment did not affect fractional anisotropy (FA), but did lead to long‐term reductions of mean diffusivity (MD) in both the cerebellum and corpus callosum. AIE resulted in increased anxiety‐like behavior and diminished object recognition memory, the latter of which was positively correlated with DTI measures. Across aging, whole brain volumes increased, as did volumes of the corpus callosum and neocortex. This was accompanied by age‐associated AD reductions in the cerebellum and neocortex as well as RD and MD reductions in the cerebellum. Further, we found that FA increased in both the cerebellum and corpus callosum as rats aged from P80 to P220. Thus, both age and AIE treatment caused long‐term changes to brain structural integrity that could contribute to cognitive dysfunction. Abstract : Binge drinking is common during adolescence and can have deleterious effects on brain maturation. Using diffusion tensor imaging (DTI), we discovered that adolescent rats exposed to the adolescent intermittent ethanol (AIE) model of human binge drinking alters adult brain structural integrity in the cerebellum, corpus callosum, hippocampus, and neocortex. AIE increased anxiety‐like behavior and impaired object recognition memory, which was correlated with DTI. Thus, AIE treatment caused long‐term changes to brain structural integrity that could contribute to cognitive dysfunction.